Development of Repeatable Arrays of Proteins using Immobilized DNA Microplate (RAPID-M) Technology - Ashaari, Nur Suhanawati; Ramarad, Suganti; Khairuddin, Dzulaikha; Mat Akhir, Nor Azurah; Yuka, Hara; Mahadi, Nor Muhammad; Rahmah, Mohamed; Nathan, Sheila (BioMed Central, 2015)
Background Protein microarrays have enormous potential as in vitro diagnostic tools stemming from the ability to miniaturize whilst generating maximum evaluation of diagnostically relevant information from minute amounts of sample. In this report, we present a method known as repeatable arrays of proteins using immobilized DNA microplates (RAPID-M) for high-throughput in situ protein microarray fabrication. The RAPID-M technology comprises of cell-free expression using immobilized DNA templates and in situ protein purification onto standard microarray slides. Results To demonstrate proof-of-concept, the repeatable protein arrays developed using our RAPID-M technology utilized green fluorescent protein (GFP) and a bacterial outer membrane protein (OmpA) as the proteins of interest for microarray fabrication. Cell-free expression of OmpA and GFP proteins using beads-immobilized DNA yielded protein bands with the expected molecular sizes of 27 and 30 kDa, respectively. We demonstrate that the beads-immobilized DNA remained stable for at least four cycles of cell-free expression. The OmpA and GFP proteins were still functional after in situ purification on the Ni–NTA microarray slide. Conclusion The RAPID-M platform for protein microarray fabrication of two different representative proteins was successfully developed.